Modalities for assessing the nutritional status in patients with diabetes and cancer. (August 2018) - Clemente, G.; Gallo, M.; Giorgini, M.; ,
Abstract: Epidemiological data have shown that an increased body mass index (BMI) is associated with a higher risk of various cancers, especially in obese diabetic patients. However, oncologic patients often present nutritional alterations that can worsen their prognosis. The aim of this review is to propose the use of cheaper and easy to use tools to assess the nutritional status of patients with cancer with altered glucose metabolism. Based on a literature review, we propose anthropometric measures to classify the degree of malnutrition. Moreover, the Karnofsky Performance Status (KPS) and the Eastern Cooperative Oncology Group's performance index (ECOG) are useful to assess the functional status of the body; the achievement of nutritional needs can be analysed with the PG-SGA questionnaire, while the quality of life can be investigated using the DTSQ, SF36, EQ-5D questionnaires and the Edmonton Symptom Assessment System. Pre-albumin dosage and lymphocyte count are proposed as nutritional parameters. The degree of hydration can be evaluated through the Bio-Impedance Test (BIA), and energy intake through the dairy food diary, which considers the type of nutrition and the consistency of the meals. It is possible to use a score for each tool used, which is useful to plan an adequate nutritional intervention.